1977
DOI: 10.1021/bi00635a026
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of guanidinated cytochrome c by carbon-13 nuclear magnetic resonance spectroscopy

Abstract: in which the longest decay component could be unambiguously determined, these measurements represent an important check on the validity of the conclusions drawn from the anti-DNS studies. Furthermore, the measurements were carried out on an antibody population with a different specificity. Thus, Fab segmental flexibility is probably generally present in IgG molecules. 19 homoarginine residues are distributed over a range of about 1 ppm and include two discrete single guanido carbon resonances. Distinct changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…When L-arginine is incorporated into position 63 of STI, the Cl shifts -0.24 ppm (upfield); upon subsequent formation of the STI-trypsin complex, the Arg63 Cf shifts +0.23 ppm (downfield). These environmental shifts are comparable to those reported by Oldfield et al (1975) for several small proteins but are smaller than some found recently for [13C']-L-homoarginine and pC*]-L-arginine in other proteins (Stellwagen et al, 1977;Cocco et al, 1977). In the latter studies, a paramagnetic heme group (Stellwagen et al, 1977) or a large aromatic nucleotide ligand (Cocco et al, 1977) was present.…”
Section: Discussionsupporting
confidence: 81%
“…When L-arginine is incorporated into position 63 of STI, the Cl shifts -0.24 ppm (upfield); upon subsequent formation of the STI-trypsin complex, the Arg63 Cf shifts +0.23 ppm (downfield). These environmental shifts are comparable to those reported by Oldfield et al (1975) for several small proteins but are smaller than some found recently for [13C']-L-homoarginine and pC*]-L-arginine in other proteins (Stellwagen et al, 1977;Cocco et al, 1977). In the latter studies, a paramagnetic heme group (Stellwagen et al, 1977) or a large aromatic nucleotide ligand (Cocco et al, 1977) was present.…”
Section: Discussionsupporting
confidence: 81%
“…The NE-acetimidyl derivatives of [Hse65lcytochrome c were prepared by the method of Wallace & Offord (1979). NE-Amidino-cytochrome c was prepared in accordance with published procedures (Hettinger & Harbury, 1964;Stellwagen et al, 1977) by the reaction of 0methylisourea hydrogen sulphate with cytochrome c (type III). The modified protein was purified in the same manner as N'-acetimidyl-cytochrome c. Amino acid analysis of the major product indicated that the reaction was > 98% complete.…”
Section: Methodsmentioning
confidence: 99%
“…The average chemical shift observed for each of these envelopes is identical with those observed in a SDS-denatured sample, indicating that these lysines are all surface residues and readily accessible to the solvent. Stellwagen et al (1977) and Cocco et al (1978) have observed relationships between the chemical shift and segmental motion (as measured by T{s) of surface-exposed residues; i.e., a residue experiencing decreased motion will also be chemically shifted the furthest from the position of the solvent-exposed residues. We have been unable to detect any significant differences in the spin-lattice relaxation times of the shoulders of these two envelopes which suggests that all residues which comprise each envelope do indeed relax similarly.…”
Section: Methodsmentioning
confidence: 99%
“…We have been exploring ways which may be used to examine these protein-cell interactions using high-resolution NMR techniques; one approach is to label surface residues on Con A with NMR-active nuclei which might be sensitive to interactions occurring between the protein and a cell surface. Stellwagen et al (1977) converted the surface lysines of cytochrome c to homoarginine residues by using 90% [13C]-<9methylisourea and showed that the resulting 13C resonances were sensitive to the chemical environment and segmental motion experienced by each homoarginine residue. Biological methods have been successfully used to label dihydrofolate reductase with [13C]arginine (Cocco et al, 1978).…”
mentioning
confidence: 99%